Commercial banking as a key factor for SMEs development in Mexico through factoring: A qualitative approach - Guillermo Pérez-Elizundia; José Alfredo Delgado-Guzmán; Jesús F. Lampón (European Research on Management and Business Economics (ERMBE), 2020)
Despite the advantages that literature grants to factoring, its degree of adoption in small and medium-sized enterprises (SMEs) is low. The objective of the research is to establish the determinants in factoring adoption that allow greater access to financing by SMEs. For this purpose, a qualitative study was carried out through in-depth interviews with ten financial entities in Mexico that represent between 60 and 80% in volume of factoring that is operated in the country. Aspects such as legal certainty, efficient customer information systems, the reduction of requirements to start operations or the ease of operation and simplification of procedures are key in the design and implementation of factoring programs. The implications for financial institutions and public administration are to design factoring programs with a vision beyond the commercial aspect and define a robust legal framework to operate this financial product.
Keywords: M10; M19; M110; G30; G32; 650; Factoring; Mexico; Supply chain finance; Working capital management